2017
DOI: 10.1007/s12328-017-0728-1
|View full text |Cite
|
Sign up to set email alerts
|

A resected case of two branch duct-type intraductal papillary mucinous neoplasms showing different clinical courses after a two-year follow-up

Abstract: The patient was a 60-year-old man without any particular complaints, but he underwent abdominal computed tomography (CT) and magnetic resonance cholangiopancreatography (MRCP) due to a fatty liver, which revealed two similar cystic lesions regarded as branch duct-type intraductal papillary mucinous neoplasm (BD-IPMN) in the pancreatic body [BD-IPMN (b), 16 mm in size] and tail [BD-IPMN (t), 13 mm in size] without a “high-risk stigmata” or “worrisome features”. He subsequently received follow-up by MRCP every 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In most cases, these tumors are diagnosed after progression to invasive cancer 5 . Therefore, high‐grade dysplasia of pancreatobiliary‐type IPMN, as demonstrated in this case, has rarely been reported 6 …”
Section: Case Report and Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In most cases, these tumors are diagnosed after progression to invasive cancer 5 . Therefore, high‐grade dysplasia of pancreatobiliary‐type IPMN, as demonstrated in this case, has rarely been reported 6 …”
Section: Case Report and Discussionmentioning
confidence: 89%
“…5 Therefore, high-grade dysplasia of pancreatobiliary-type IPMN, as demonstrated in this case, has rarely been reported. 6…”
Section: Case Report and Discussionmentioning
confidence: 99%
“…These genes could promote tumor growth and progression by repressing apoptosis instead of cell proliferation (46). A case study on a resected two-branch duct-type IPMNs showed concurrent activation of genes in the same family (MUC5AC and MUC6), for high-grade dysplasia (54). Thus, we believe that an extension to study the whole MUC family could reveal biological evidence for IPMNs grading, which is worth exploring in future research.…”
Section: 2) Ti-mutanet Suggests Clinically Relevant Biomarkers For St...mentioning
confidence: 92%